2000
DOI: 10.1111/j.1365-2133.2000.03717.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital lichen sclerosus associated with morphoea or systemic sclerosis: clinical and HLA characteristics

Abstract: Although patients with both morphoea and lichen sclerosus have been reported previously, in the majority of these reports the lichen sclerosus has been extragenital. We report nine patients in whom genital lichen sclerosus coexisted with scleroderma spectrum disorders including seven with morphoea, one with morphoea and lichen planus, and one with systemic sclerosis. The clinical features, associated autoimmune disease, autoantibodies and HLA type are reported. Antibodies to Borrelia burgdorferi were not detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Correlation with serologic data was reported by Schempp et al who detected Borrelia DNA in skin biopsies of all nine patients, but a negative serology for B. burgdorferi 13 . Other studies based on serologic data did not suggest an association of morphea with Borrelia infection 21,31 . Also in our patient with Borrelia‐DNA positive morphea, serologic assays were negative.…”
Section: Discussionsupporting
confidence: 85%
“…Correlation with serologic data was reported by Schempp et al who detected Borrelia DNA in skin biopsies of all nine patients, but a negative serology for B. burgdorferi 13 . Other studies based on serologic data did not suggest an association of morphea with Borrelia infection 21,31 . Also in our patient with Borrelia‐DNA positive morphea, serologic assays were negative.…”
Section: Discussionsupporting
confidence: 85%
“…This fact could suggest that LS usually precedes morphea. The association between morphea and LS has been reported previously, mainly in patients with plaque morphea, [34][35][36][37][38][39][40] but it was reported only once in a case of linear monomelic morphea in a young boy. 40 In most cases, however, the LS was extragenital.…”
Section: Commentmentioning
confidence: 93%
“…40 In most cases, however, the LS was extragenital. 35,[37][38][39]41 Only 1 study 35 reported 7 cases of patients with morphea and genital LS. The fact that 38% of patients with morphea have associated genital LS strongly supports the fact that these 2 diseases share common pathogenetic pathways, and possibly a common genetic background, if they are not one and the same disease.…”
Section: Commentmentioning
confidence: 99%
“…Hallopeau considered the disorder to be a type of lichen planus and other clinicians thought the condition was related to well circumscribed scleroderma. Although cases have been reported of LS coexisting with lichen planus and localized scleroderma 2 most clinicians now regard LS as a separate entity.…”
Section: Discussionmentioning
confidence: 99%